Locomotive to aeromotive : Octave Chanute and the transportation revolution - Short, Simine, 1944- (University of Illinois Press, 2011)
Drawing on a rich trove of archival material and exclusive family sources, this is a detailed examination of Chanute's life and his immeasurable contributions to the fields of engineering and transportation, from the ground transportation revolution of the mid-19th century to the early days of aviation.